2010
DOI: 10.1093/teamat/hrq002
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the mathematical competency of university entrants in Ireland by leaving certificate mathematics grade

Abstract: This article reports on the mathematical competency of students entering third-level education in the University of Limerick (UL). Data from diagnostic testing, gathered on 5,949 students between the years 1998 and 2008, are used to demonstrate the changes in competency levels of students entering UL. There has been a significant decline in the performance of students in the diagnostic test over time. The performance, on average, of students with the same leaving certificate mathematics grade on entry into uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…This is especially true when analysing the performance of students who had previously achieved C2 and C3 grades at higher level in the leaving certificate, and A1, A2, and B2 grades at ordinary level in the leaving certificate. These findings are surprising, given that Faulkner et al [19] completed similar analysis of this database for the years 1998-2008 and found no evidence of varying diagnostic test performance per leaving certificate mathematics grade. She concluded that the 'Leaving Certificate Examination is awarding the same grade for a similar average level of mathematical ability as it was ten years ago.…”
Section: Comparison Of Students With Similar Leaving Certificate Mathmentioning
confidence: 80%
See 1 more Smart Citation
“…This is especially true when analysing the performance of students who had previously achieved C2 and C3 grades at higher level in the leaving certificate, and A1, A2, and B2 grades at ordinary level in the leaving certificate. These findings are surprising, given that Faulkner et al [19] completed similar analysis of this database for the years 1998-2008 and found no evidence of varying diagnostic test performance per leaving certificate mathematics grade. She concluded that the 'Leaving Certificate Examination is awarding the same grade for a similar average level of mathematical ability as it was ten years ago.…”
Section: Comparison Of Students With Similar Leaving Certificate Mathmentioning
confidence: 80%
“…Taking into account these findings, one would expect that students from each cohort analysed between 2003 and 2013 would perform the basic mathematical skills tested through the previously outlined diagnostic test at similar levels. This expectation was largely due to the conclusion drawn by Faulkner et al [19] that students entering UL with particular leaving certificate mathematics grades performed to a similar level in the diagnostic test between 1998 and 2008. However, such consistency in performance was not present when the data gathered between 2003 and 2013 were analysed.…”
Section: Profiling Beginning Undergraduates' Mathematical Backgroundsmentioning
confidence: 96%
“…However, given that these factors have previously been explored, both in a range of other studies (e.g. Faulkner et al 2016;Faulkner et al 2010), as well as in a general report on this study (O'Sullivan et al 2014), the focus of this paper will be the differences in engagement based on gender.…”
Section: Engagement With Mathematics Supportmentioning
confidence: 97%
“…Much of this concern has focused on the longstanding mathematical under-preparedness of incoming third level students, as issue which is regularly referred to as the 'Maths Problem' (Howson et al, 1995). This phenomenon in which students are under-prepared for the mathematical demands of their undergraduate course, dates back many decades and has been reported in countries such as Ireland (Cleary, 2007;Faulkner et al, 2010), the U.K. (Edwards, 1995;Lawson, 2003), and more recently Portugal (Carr et al, 2015). The 'Maths Problem' is characterised by beginning undergraduates displaying a lack of basic mathematical skills, as well as fragmented understanding, inadequate concept knowledge, and an inability to successfully solve mathematical problems (Rylands & Coady, 2009;Gill, O'Donoghue, Faulkner, Hannigan, 2010).…”
Section: Introductionmentioning
confidence: 94%